Comparative analysis of electrode, preheat, and interpass combination in dissimilar GMAW welding of bisalloy 400 steel and SM490YA material on hardness and micro structure - Munir, Moh. Miftachul; Kusminah, Imah Luluk; Kamilah, Nadhifatul (Politeknik Negeri Lhokseumawe, 2024)
A construction company produced a side-dump type trailer used to transport coal, but it suffered damage in the form of cracks in the welding joints on the floor. The weld joint uses two different materials, Bissalloy 400 and SM490YA steel. This study aims to analyze the damage and repair it using appropriate electrodes, preheating, and interpass temperature, which affect the hardness and microstructure of both materials. The hardness test results showed that the highest value reached 385 HVN. Increasing the preheat and interpass temperatures was found to decrease the material's hardness. Microstructure analysis revealed phase changes in the weld metal, including mixing of martensite phase, ferrite phase, and pearlite phase. The use of a buffer layer between dissimilar materials proved effective in reducing the risk of cracking and deformation. This research confirms the importance of selecting appropriate welding parameters to improve joint quality in materials with significant carbon equivalent differences.